An overview of science, technology, and innovation (STI) policy for driving a manufactured-led economic and social transformation of Nigeria - Igbinovia, Famous Oghomwen; Křupka, Jiří (International Business Information Management Association-IBIMA, 2019)
This article provides an overview of science, technology and innovation (STI) policy that are central to the broader vision of Nigeria's manufactured-led economic and social transformation agenda. The realization of development goals requires a meticulous process of policy making. However, in several developing countries such as Nigeria, there is discontinuity between policy and development preference as most policies are not based on scientific facts either due to the reason that they are unavailable or, where they exist, unreliable. Using a system analysis framework, this article brings into prospect the essential role played by STI indicators in providing scientific proof for designing, formulating and implementing national innovation policy for a manufactured-led economic and social transformation of Nigeria. This can serve as a structure for utilizing scientific proof in policy making in a developing country frame of reference. This article is issued as part of a thematic collection on scientific advice to governments. The reason for STI in Nigeria's manufactured-led economic and social transformation agenda is that only when knowledge is changed into products and processes and utilized by the society in an economically and socially significant way, that it becomes an innovation.
Přehled politik ve vědě, technologii a inovaci pro řízení výroby a ekonomické a sociální transformace v Nigérie
Keywords: Innovation; manufacturing; economy of Nigeria; social transformation; technology; Inovace; výrobní; hospodářství Nigérie; sociální transformace; technologie